A STUDY ON THE SPEAKING ABILITY OF THE FIRST YEAR STUDENTS OF “SMK TARUNA PEKANBARU” - Khasanah Nur Darozah; Eliwarti Eliwarti; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This descriptive research aims to find out the students’ ability level in learning speaking of “SMK Taruna Pekanbaru”. The population of this research was the first year students of SMK Taruna Pekanbaru in the academic year of 2021/2022. The samples were the students of TBSM consists of 33 students who have been selected using cluster random sampling technique. The data were collected by using speaking test. The speaking tests were analyzed using a speaking assessment by Brown (2004). As a result of the research, it was found that the first year students’ ability level in speaking using complimenting metrial were classified as poor level (53). The first year students’ ability were found in the aspect of the pronunciation (51,2), grammar (53,7), vocabulary (52), fluency (53), and comprehension (55). Thus, in other words, it can be concluded that students’ ability in speaking by the second year students of SMK Taruna Pekanbaru were classified into poor level (53).Key Words: Ability, Speaking, Complimenting.